Una teologia che serve: Appunti di lavoro - Duchi, Simone (Rassegna di teologia, 2025)
The essay deals with the meaning of the profession that the theologian carries out, reflecting on its conditions of possibility and fundamental implications. Before the academic profession, as its raison d'être, there is indeed another profession, that of faith. In this regard, only the awareness that the theologian can, will and must mature structures the adequate spirituality for his commitment.